2018
DOI: 10.1038/s41598-018-22026-0
|View full text |Cite
|
Sign up to set email alerts
|

PV1, a novel Plasmodium falciparum merozoite dense granule protein, interacts with exported protein in infected erythrocytes

Abstract: Upon invasion, Plasmodium falciparum exports hundreds of proteins across its surrounding parasitophorous vacuole membrane (PVM) to remodel the infected erythrocyte. Although this phenomenon is crucial for the parasite growth and virulence, elucidation of precise steps in the export pathway is still required. A translocon protein complex, PTEX, is the only known pathway that mediates passage of exported proteins across the PVM. P. falciparum Parasitophorous Vacuolar protein 1 (PfPV1), a previously reported para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…1C). In merozoites, mCherry fluorescence was concentrated in a punctate intraparasitic region, perhaps signifying storage of PbPV5 in the dense granules, as has been demonstrated for several other important PV proteins (30)(31)(32), but this fraction was minimal as compared to the protein contained in the residual body. Quantification of the mCherry-fluorescence intensity in live parasites indicated that PbPV5 is much more abundant in mature parasite stages than in rings and merozoites, suggesting substantial levels of de novo synthesis throughout parasite maturation (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…1C). In merozoites, mCherry fluorescence was concentrated in a punctate intraparasitic region, perhaps signifying storage of PbPV5 in the dense granules, as has been demonstrated for several other important PV proteins (30)(31)(32), but this fraction was minimal as compared to the protein contained in the residual body. Quantification of the mCherry-fluorescence intensity in live parasites indicated that PbPV5 is much more abundant in mature parasite stages than in rings and merozoites, suggesting substantial levels of de novo synthesis throughout parasite maturation (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…Therefore, the molecular mediated parasites residing in the host cell might be fewer and more infertile for Babesia than Plasmodium spp. In Plasmodium spp., many proteins were reported to be discharged into the cytoplasm or cytoplasmic face of iRBC to internalize and stabilize the host cell environment for parasite survival and replication [ 16 18 , 52 54 ]. For example, ring-infected erythrocyte surface antigen (RESA) proteins were secreted by dense granules, and then were located to the cytoplasmic face of iRBC through binding the repeat 16 of beta-chain for stabilizing the spectrin tetramer against mechanical and thermal damage [ 16 , 17 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dense granules are reported to release proteins into the parasitophorous vacuole (PV) shortly after invasion, which may play a key role in PV membrane modifications and is assumed to be associated with the nutrient acquisition. Likewise, the proteins secreted by dense granules are also translocated to the cytoplasmic side of infected red blood cell (iRBC) and participate in stabilizing spectrin tetramers [ 15 18 ]. However, in Babesia spp.…”
Section: Introductionmentioning
confidence: 99%
“…To generate a parasite line expressing PfRipr-HA, full length pfripr was amplified by PCR with the primers indicated in Table S2 (Ripr-tran F and R). The DNA fragments were digested with SpeI and PstI, and ligated into pD3HA plasmids with a Pfef1-alpha promoter for episomal expression 52,53 . For transfection, parasitized erythrocytes were resuspended in 200 µl of cytomix (120 mM KCl, 0.15 mM CaCl 2 , 2 mM EGTA, 5 mM MgCl 2 , 10 mM K 2 HPO 4 /KH 2 PO 4 , 25 mM HEPES, pH 7.4) containing 100 µg of plasmid DNA.…”
Section: Scientific Reports |mentioning
confidence: 99%